Maqasid Al-Shariah sebagai Kerangka Etis dalam Pengembangan Kebijakan Sosial Keumatan - Nurul Hidayah; Ahmad Syafii; Rizki Pratama; Imam solihin (Al-Jinan : Jurnal Studi Islam, 2026)
This study investigates the application of Maqashid al-Shariah as an ethical framework for developing community-oriented social policies in Indonesia. The background lies in the inadequacy of secular policy frameworks in addressing the spiritual, moral, and communal dimensions of Muslim community welfare, particularly amid rising socioeconomic inequalities. The purpose is to analyze the five classical objectives of Islamic law preservation of religion, life, intellect, lineage, and property as operational principles for formulating inclusive and just social policies. Using a qualitative library research approach combined with normative-analytical methods, this study examines classical and contemporary fiqh literature, national policy documents, and scholarly works on Islamic social ethics. Findings reveal that Maqashid al-Shariah provides a comprehensive and humanistic ethical framework that transcends the limitations of both purely secular and narrowly legalistic policy approaches. The study concludes that systematic integration of Maqashid al-Shariah into social policy discourse can significantly enhance policy effectiveness and social justice outcomes in Indonesian Muslim communities.